Effect of dietary Clostridium butyricum supplementation on growth performance, immune function, and intestinal health of hybrid grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂) - Chen, Weijun; Song, Tao; Li, Dong; Chen, Mingfan; Wang, Pan; Ye, Jidan (Frontiers in Immunology, 2025)
IntroductionThe aim of this study is to investigate the effects of supplementing Clostridium butyricum (C. butyricum) on hybrid grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂), with a particular focus on its impact on growth performance, blood composition, intestinal antioxidant capacity, gut microbiota, tight junction protein (ZO-1) expression, and inflammatory gene expression. The study seeks to uncover the potential health benefits of C. butyricum supplementation for hybrid grouper.MethodsThe experiment included four groups: a control group (CON) and three experimental groups, each supplemented with different strains of C. butyricum (KM, DZN, and CLH), with a concentration of 1 × 10⁷ colony-forming units per gram. These groups were designated as CB1 (KM), CB2 (DZN), and CB3 (CLH). The study evaluated growth performance, blood composition, intestinal antioxidant capacity, gut microbiota, ZO-1 protein expression, and inflammatory gene expression (IL-1β and Ikk-β).ResultThe results indicated that supplementation with C. butyricum had no significant effect on body weight gain (WG), feed efficiency (FE), or body composition. However, the CB3 group significantly increased the activity of superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) in the intestine, as well as the expression of ZO-1. In addition, the CB3 group significantly increased serum lysozyme (LZM) activity, complement 4 (C4) levels, and immunoglobulin M (IgM) concentration, while significantly reducing the expression of pro-inflammatory genes (IL-1β and Ikk-β). After supplementation with C. butyricum, the level of malondialdehyde (MDA) in the intestine was significantly lower than that in the control group, indicating a reduction in intestinal oxidative stress. Supplementation with C. butyricum also altered the composition of the gut microbiota, promoting the growth of beneficial bacteria and inhibiting pathogenic bacteria, thereby further enhancing ZO-1 expression and intestinal barrier function.DiscussionThis study suggests that supplementing C. butyricum has a significant immunomodulatory effect on hybrid grouper, enhancing serum immune parameters, alleviating intestinal inflammation and oxidative stress, and promoting intestinal health. Although no significant impact was observed on growth performance, the role of C. butyricum in improving intestinal barrier function and modulating the gut microbiota highlights its potential for enhancing fish health.